Multi-energy Network Model of Virtual Energy Router - Chen, Yang; Zhang, Luqing; Chen, Aikang; Zhang, Yanchi; Xie, Da (E3S web of conferences, 2019)
Energy router is the main equipment of energy Internet to interact through energy and information. This paper proposes the routing algorithm of the virtual energy router composed of multiple energy routers and constructs the multi-energy coupling correlation model, and combines internal routing algorithm of the virtual energy router with multi-energy correlation model to plan the capacity of energy routers in the regional energy network composed of multiple parks. The simulation shows that the planning method based on the routing algorithm improves the energy, environment and economic benefits of the regional energy wide area network.